DETERMINATION OF THE INFLUENCE OF RANDOM FACTORS ON THE QUALITY AND RELIABILITY OF POWER SUPPLY - Popescu V.S. (Problems of the Regional Energetics)
The operation of power networks is accompanied by a number of issues including the key issue is the reliability of these networks. At the present stage in the transmission and distribution of electricity held a significant number of disconnections, subject to various random factors of influence. The problem of ensuring continuity and quality of electricity supply to consumers is a fairly current Republican power generation and its solution is imperative to know the influence factors and their impact on the reliability of the equipment installed in the electrical network. This paper is dedicated to the criteria for assessing the impact of influence factors on the reliability of electrical networks and forecasting mechanism and continuity of power supply to consumers.